Between Convenience and Risk: A Legal Analysis of Consumer Protection in Pay Later Services - Wardah, Siti Syarifah Wafiqah; Kasmita, Maya; Irensi Seppa, Yusi (Jurnal Administrasi Bisnis, 2025)
Paylater services have grown significantly in Indonesia as a practical payment alternative in the digital era. However, along with its growth, various challenges related to consumer protection have emerged, especially in terms of transparency of fees, interest, and personal data management. This research aims to analyze the aspects of consumer protection in paylater services in Indonesia, as well as identify legal gaps that exist in applicable regulations, including the Consumer Protection Law, Electronic Information and Transactions law, and Financial Services Authority Regulations. The method used is a normative approach with analysis of laws and regulations and related literature. The results show that current regulations have not specifically regulated paylater services, resulting in a legal vacuum in consumer protection, including a lack of cost transparency and adequate supervision. This research is relevant to encourage regulatory improvements, stricter supervision by financial services authorities, and consumer education about their rights so that paylater services can operate with the principles of fairness and better protection.                       Keywords: Paylater Service, Consumer Protection, Legal Regulation